Governance landscapes for emerging technologies: The case of cryptocurrencies. Issue 4 (5th November 2020) - Whitford, Andrew B.; Anderson, Derrick
Abstract: Scholars call for "adaptive governance" to balance concern about technology uncertainty with the need for innovation in the governance of emerging technologies. Yet, empirical assessment of such governance systems remains sparse. Do the actors interested in the potential regulation of an emerging technology focus on their own interests and opportunities, or do they think in terms of the collective interest? We focus on the actors who embed such systems from a novel landscape perspective that combines two dimensions of governance: the nature of the regulatory target, and the nature of the process they advocate for governing the target. We present data from over 70 actors in the area of cryptocurrencies for evaluating this new logic.